Ferromagnetic Order in the Intermetallic Alloys laNi5-xMgx - D.N Ba; L.T Tai; N.T Trung; N.T Huy (Universitas Gadjah Mada, 2012)
The influences of the substitution of Ni with Mg on crystallographic and magnetic properties of the intermetallic alloys LaNi5-xMgx (x ? 0.4) were investigated. The X-ray diffraction patterns showed that all samples were of single phase, and the lattice parameters, a and c, decreased slightly upon chemical doping. LaNi5 is well known as an exchange-enhanced Pauli paramagnet. Interestingly, in LaNi5-xMgx, the ferromagnetic order existed even with a small amount of dopants; the Curie temperature reached the value of room temperature for x = 0.2, and enhanced with increasing x.